Biotransformation of ω fatty acids using pseudomonas aeruginosa - Omar, Muhammad Nor (2012)
Biotransformation of fish oil containing ω fatty acids using Pseudomonas spp has been carried out. In the present study, Pseudomonas aeruginosa was used to transform ω fatty acids, extracted from Malaysian catfish Clarias batrachus, into useful metabolite. The fatty acids were extracted from the freeze-dried catfish flesh using a modified Folch method with the chloroform and methanol system. The crude oil was added to the bacterial culture and incubated at 28oC for 4 days. After incubation, the biotransformed product was extracted and analyzed by using gas chromatography and mass spectrometer (GC-MS) to identify the fatty acids and other compounds. It was found that several fatty acids, especially ω-fatty acids were converted to hydroxyl fatty acids. This indicates that ω-fatty acids can be used as starting materials for other bioactive metabolites for pharmaceutical purposes.